Lattice distortion induced Ce-doped NiFe-LDH for efficient oxygen evolution - Liao, Yuanyuan; He, Ruchen; Pan, Wanghao; Li, Yao; Wang, Yingying; Li, Jing; Li, Yongxiu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Inducing lattice distortion in NiFe-LDH nanosheets by Ce-doping towards accelerating electrocatalytic oxygen evolution reaction.•The optimal NiFeCe-LDH@CP only requires 267 mV to deliver 100 mA cm−2, which is 41 mV lower than pure NiFe-LDH@CP.•NiFeCe-LDH@CP have retained their structural property after 70 h stability.•DFT calculations reveal that lattice distortion could optimize the electronic structure of the Ni element in active sites and lower the energy barrier, thus accelerating the OER. Nickel-iron layered double hydroxide (NiFe-LDH) is a promising active electrocatalyst for oxygen evolution reaction (OER). However, the development of NiFe-LDH is limited by poor electrical conductivity and inferior cycling stability. Herein, we present a structural perturbation and distinct distorted lattice strategy via Ce doping in NiFe-LDH on carbon paper (CP) (NiFeCe-LDH@CP) to boost its OER performance. Lattice distortion results in a large accessible surface area and induces more Ovac, accelerating the OER by modifying the intrinsic electronic structure and optimizing the adsorption energy of intermediates. As a result, the optimized NiFeCe-LDH@CP possesses excellent stability over 70 h and can deliver the current density of 100 mA/cm2 with the overpotentials of only 267 mV, which is 41 mV lower than pure NiFe-LDH@CP. Theoretical calculations indicate that the introduction of lattice distortion into NiFe-LDH could optimize the electronic structure of the Ni element in active sites and lower the energy barrier, thus leading to a significant increase in OER activity. This work figures out the effect of lattice distortion strategy on the improvement of OER performance, which opens new perspectives on the development of defect-rich OER electrocatalysts.